Ethical Leadership insight factor: Does it matters Ethical Climate and Organizational Commitments to step behavior towards maximum goals? - Putri Sintyaningsih; Astrid Puspaningrum; Agung Yuniarinto; Jumadi Jumadi; Mochamad Soelton; Tine Yuliantini (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine the influence of Ethical Leadership on Job Satisfaction, Ethical Climate and Organizational Commitment at Frontliner Passenger Service West Region PT Kereta Commuter Indonesia. Data collection techniques are done by distributing questionnaires using ordinal scales. This research was conducted on 66 respondents by using quantitative descriptive approach and hypothesis testing. The collected data is then analyzed using the technique analysis Structural Equation Modeling (SEM) through SmartPLS (Partial Least Square) software. The results of this study show that Ethical Leadership positively and significantly influence on Ethical Climate, Job Satisfaction and Organizational Commitment at Frontliner Passenger Service West Region PT Kereta Commuter Indonesia.